2020
DOI: 10.1097/mcg.0000000000001458
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Mortality in Geriatric Patients Admitted for Inflammatory Bowel Disease Management

Abstract: The goal of this study was to evaluate the inpatient mortality risk among geriatric patients with inflammatory bowel disease (IBD).Background: The challenges of caring for elderly patients with IBD will increase with the aging of the US population. Given the complications of hospitalization, we set to examine if elderly patients age older than 65 were at higher risk of mortality.Materials and Methods: All patients with ulcerative colitis (UC) or Crohn's disease (CD) in the National Inpatient Sample (NIS) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…It has been estimated that 25–30% of the IBD population are aged 60 or older, 26 making this predictor even more clinically relevant. Among inpatients, the elderly are at higher risk of poor outcomes, 4 , 27 with advanced age (≥ 65) being associated with increased inpatient mortality in IBD. 4 , 6 , 27 Interestingly, immunosuppression was not a predictor for inpatient mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that 25–30% of the IBD population are aged 60 or older, 26 making this predictor even more clinically relevant. Among inpatients, the elderly are at higher risk of poor outcomes, 4 , 27 with advanced age (≥ 65) being associated with increased inpatient mortality in IBD. 4 , 6 , 27 Interestingly, immunosuppression was not a predictor for inpatient mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Among inpatients, the elderly are at higher risk of poor outcomes, 4 , 27 with advanced age (≥ 65) being associated with increased inpatient mortality in IBD. 4 , 6 , 27 Interestingly, immunosuppression was not a predictor for inpatient mortality. While this may be due to under‐documentation and/or absolute small numbers of immunosuppressed patients ( n = 63 among 1294 deaths), the preponderance of data suggests that patient‐related factors impacted outcomes more than medication use.…”
Section: Discussionmentioning
confidence: 99%
“…Independently from age, mortality in UC after the first year from diagnosis appears to be similar to that of the general population [ 117 ], but frailty [ 24 ], steroid use [ 118 ], infections [ 119 ], and surgery-related complications [ 27 ] remain the major drivers for adverse outcomes.…”
Section: Therapy-related Risks In Older Patients With Ucmentioning
confidence: 99%
“…[18][19][20][21][22] Studies centered on elderly IBD patients repeatedly found increased mortality rates. 10,23,24 Studies on the Inflammatory Bowel South-Eastern Norway [IBSEN] cohort detected a small but not significant increase in mortality 20 years after diagnosis. 25,26 While the proportion of elderly patients in this cohort has grown, the aims of this study were primarily to determine the hazard ratios [HRs] for mortality within 30 years following diagnosis, and secondarily to identify specific causes of mortality and subgroups of patients most at risk.…”
Section: Inflammatory Bowel Diseases [Ibd] Including Crohn's Diseasementioning
confidence: 99%
“… 18–22 Studies centered on elderly IBD patients repeatedly found increased mortality rates. 10 , 23 , 24 …”
Section: Introductionmentioning
confidence: 99%